Aspekte der Kunst in Schleswig-Holstein 1980-1990 - Lempelius, Uwe; Rathke, Christian; Schulte-Wülwer, Ulrich; Siewert, Roswitha; Sonderjylands Kunstmuseum, Tonder Museum, Tondern (Schleswig : Schleswig-Holsteinische Landesmuseum - Schloss Gottorf, 1991)
Arlt, Elsbeth ; Borgwardt, Heidrun ; Charmi, Shahin ; Doose, Erwin ; Fischer, Lili ; Goffin, René ; Grau, Juro ; Hlináková, Zuzana ; Jäger, Hanna ; Koblasa, Jan ; Koswig, Dieter ; Kunde, Helmut ; Nagel, Peter ; Petermann, Ulf ; Schulte-Wülwer, Annemarie ; Siebenrok, Chris ; Thode, Joachim ; Wassermann, Gudrun
Aspekte der Kunst in Schleswig-Holstein 1980-1990, Schleswig-Holsteinische Landesmuseum - Schloss Gottorf, 20.1. - 17.2.1991 ; Sonderjylands Kunstmuseum, Tonder Museum, Tondern DK, 11.5. - 16.6.1991
boek